If I say if : the poems and short stories of Boris Vian - Vian, Boris, 1920-1959 (University of Adelaide Press, 2014)
Boris Vian is a rare phenomenon. Nothing short of a national treasure in France, he is hardly known overseas. In his lifetime, he divided literary opinion with masterpieces that failed to sell and best sellers that caused outrage, trials and even deaths, including his own. As an impresario, he became the figurehead of the jazz scene that marked the French left bank at the end of the Second World War and was responsible for bringing Duke Ellington and Miles Davis to France. As a musician, he played his trumpet against the advice of cardiologists, sang pacifist songs before audiences of outraged patriots and, in passing, created French rock 'n' roll. Posthumously, he became known for his theatre, film scripts and poetry as well as for his novels. And in May '68 he became a revolutionary icon. In two posthumously published collections of short stories, translated for the first time in English in this volume, the France of Jean-Paul Sartre and Simone de Beauvoir is seen through Vian's idiosyncratic and often rather madcap lens. And alongside them there is another voice entirely, a side of Vian that blends his dry irony with deep, at times startling, emotion. His poems, again published in English here for the first time, give a counter-point to the public figure loved throughout France but never quite admitted into the Pantheon of her great artists. For those who may have read L'Ecume des jours or J'irai cracher sur vos tombes, or heard someone singing "Le Deserteur" on the Paris Metro, or for those who are discovering him for the first time, here are both sides of the incomparable and never quite self-coinciding Boris Vian.